Microstructure, mechanical and tribological behavior of hot-pressed mechanically alloyed Al–Zn–Mg–Cu powders. (15th June 2015) - Azimi, A.; Fallahdoost, H.; Nejadseyfi, O.
Graphical abstract: Highlights: Nanocrystalline Al7050 alloy was synthesized by mechanical alloying. Longer milling time led to increasing porosity in hot-pressed samples. Significant improvement in strength and wear resistance was obtained by increasing the milling time up to 40 h. Abstract: This research focuses on the preparation of Al7050 alloy via mechanical alloying and hot pressing techniques. The effect of milling time on the microstructure and densification response was investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM). Furthermore, the mechanical properties of the samples including microhardness, compression strength, and wear resistance were examined as a function of milling time. The results of the experiments proved that by increasing the milling time the crystallite size was reduced, which has a significant effect on improving the mechanical properties. In addition, porosity formation increased when the milling time was increased due to reduction of the compressibility of finer particles. By increasing the milling time to more than 40 h, a relatively invariable crystallite size was obtained and it was observed that the porosities expanded in the samples. Therefore, the compressive strength, hardness, and wear resistance were enhanced up to 40 h milling time and then the strengthening effect was relatively diminished. On observing surfaces with SEM, the dominant wear mechanism was recognized as abrasion, delamination and adhesion.